Influence of process parameters on the formation of inhalable fiber dust during shredding for mechanical recycling of fiber‐reinforced organo sheets - Hopp, Matthias; Tölle, Lisa (Journal of Applied Polymer Science)

Fiber Dust Formation during the Recycling of FRP - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe international)

Faserstäube beim FVK-Recycling - Hopp, Matthias; Tölle, Lisa; Bünger, J.; Westphal, G.; Rosenkranz, N.; Monsé, C. (Kunststoffe)

Computation on Encrypted Data Using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kußmaul, Jörn; Janneck, Jonas; Kerschbaum, Florian; Bodden, Eric (ACM Transactions on Privacy and Security)
Encrypting data before sending it to the cloud ensures data confidentiality but requires the cloud to compute on encrypted data. Trusted execution environments, such as Intel SGX enclaves, promise to provide a secure environment in which data can be decrypted and then processed. However, vulnerabilities in the executed program give attackers ample opportunities to execute arbitrary code inside the enclave. This code can modify the dataflow of the program and leak secrets via SGX side channels. Fully homomorphic encryption would be an alternative to compute on encrypted data without data leaks. However, due to its high computational complexity, its applicability to general-purpose computing remains limited. Researchers have made several proposals for transforming programs to perform encrypted computations on less powerful encryption schemes. Yet current approaches do not support programs making control-flow decisions based on encrypted data. We introduce the concept of dataflow authentication (DFAuth) to enable such programs. DFAuth prevents an adversary from arbitrarily deviating from the dataflow of a program. Our technique hence offers protections against the side-channel attacks described previously. We implemented two flavors of DFAuth, a Java bytecode-to-bytecode compiler, and an SGX enclave running a small and program-independent trusted code base. We applied DFAuth to a neural network performing machine learning on sensitive medical data and a smart charging scheduler for electric vehicles. Our transformation yields a neural network with encrypted weights, which can be evaluated on encrypted inputs in \( 12.55 \,ms \) . Our protected scheduler is capable of updating the encrypted charging plan in approximately 1.06 seconds.
Keywords: Safety; Risk; Reliability and Quality; General Computer Science

Conditional Beta-Convergence by Gravity - Stöckmann, Nico (Theoretical Economics Letters)

Verteiltes Berechnen kompakter Routingtabellen in Unit Disk Graphen - Hillebrandt, Henning

Realization of Exciton‐Mediated Optical Spin‐Orbit Interaction in Organic Microcrystalline Resonators - Ren, Jiahuan; Liao, Qing; Ma, Xuekai; Schumacher, Stefan; Yao, Jiannian; Fu, Hongbing (Laser & Photonics Reviews)

Controlling exciton distribution in WS2 monolayer on a photonic crystal - Zhang, Xiu; Chen, Zhenshi; Liu, Dong; Wan, Lei; Ma, Xuekai; Gao, Tingge (Applied Physics Express)

Dynamics of phase defects trapped in optically imprinted orbits in dissipative binary polariton condensates - Wingenbach, Jan; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

The Ruelle zeta function at zero for nearly hyperbolic 3-manifolds - Cekić, Mihajlo; Delarue, Benjamin; Dyatlov, Semyon; Paternain, Gabriel P. (Inventiones mathematicae)
Abstract We show that for a generic conformal metric perturbation of a compact hyperbolic 3-manifold $$Σ $$ Σ with Betti number $$b_1$$ b 1 , the order of vanishing of the Ruelle zeta function at zero equals $$4-b_1$$ 4 - b 1 , while in the hyperbolic case it is equal to $$4-2b_1$$ 4 - 2 b 1 . This is in contrast to the 2-dimensional case where the order of vanishing is a topological invariant. The proof uses the microlocal approach to dynamical zeta functions, giving a geometric description of generalized Pollicott–Ruelle resonant differential forms at 0 in the hyperbolic case and using first variation for the perturbation. To show that the first variation is generically nonzero we introduce a new identity relating pushforwards of products of resonant and coresonant 2-forms on the sphere bundle $$SΣ $$ S Σ with harmonic 1-forms on $$Σ $$ Σ .
Keywords: General Mathematics

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Influence of curing-induced pre-deformations on the mechanical properties of adhesively bonded joints in steel-intensive mixed-material structures - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Aubel, Tobias; Matzenmiller, Anton (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Early time behavior of spatial and momentum anisotropies in kinetic theory across different Knudsen numbers - Borghini, Nicolas; Borrell, Marc; Roch, Hendrik (arXiv:2201.13294)
We investigate the early time development of the anisotropic transverse flow and spatial eccentricities of a fireball with various particle-based transport approaches using a fixed initial condition. In numerical simulations ranging from the quasi-collisionless case to the hydrodynamic regime, we find that the onset of $v_n$ and of related measures of anisotropic flow can be described with a simple power-law ansatz, with an exponent that depends on the amount of rescatterings in the system. In the few-rescatterings regime we perform semi-analytical calculations, based on a systematic expansion in powers of time and the cross section, which can reproduce the numerical findings.

A review of 100% renewable energy scenarios on islands - Meschede, Henning; Bertheau, Paul; Khalili, Siavash; Breyer, Christian (WIREs Energy and Environment)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Even anisotropic-flow harmonics are from Venus, odd ones are from Mars - Bachmann, Benedikt; Borghini, Nicolas; Feld, Nina; Roch, Hendrik (arXiv:2203.13306)
We test the ability of the "escape mechanism" to create the anisotropic flow observed in high-energy nuclear collisions. We compare the flow harmonics $v_n$ in the few-rescatterings regime from two types of transport simulations, with $2→ 2$ and $2→ 0$ collision kernels respectively, and from analytical calculations neglecting the gain term of the Boltzmann equation. We find that the even flow harmonics are similar in the three approaches, while the odd harmonics differ significantly.

Linearly shifting ferromagnetic resonance response of La0.7Sr0.3MnO3 thin film for body temperature sensors - Hou, W; Yao, Y; Li, Y; Peng, B; Shi, K; Zhou, Z; Pan, J; Liu, M; Hu, J (Frontiers of materials science)

Dataset for random uniform distributions of 2D circles and 3D spheres. - Wojciechowski, M (Data Brief)

Pattern formation in a four-ring reaction-diffusion network with heterogeneity. - Hunter, I; Norton, MM; Chen, B; Simonetti, C; Moustaka, ME; Touboul, J; Fraden, S (Phys Rev E)

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Filvan Torkaman, Najmeh; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Losing What You Never Had - Akkerman, Agnes; Manevska, Katerina; Thommes, Kirsten; Sluiter, Roderick (Employment Relations as Networks)

Investigation of leak tightness for bonded steel joints induced by mechanical and corrosive load for use in battery housings - Schmolke, Tobias; Meschut, Gerson (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Three Layers of Abstraction—A Conceptual Framework for Theorizing digital Multi-Sided Platforms - Poniatowski, Martin; Lüttenberg, Hedda; Beverungen, Daniel; Kundisch, Dennis (Information Systems and e-Business Management, Special Issue on Platform Business Models and Platform Strategies)

Property-Driven Testing of Black-Box Functions - Sharma, Arnab; Melnikov, Vitaly; Hüllermeier, Eyke; Wehrheim, Heike (Proceedings of the 10th IEEE/ACM International Conference on Formal Methods in Software Engineering (FormaliSE))
Testing is one of the most frequent means of quality assurance for software. Property-based testing aims at generating test suites for checking code against user-defined properties. Test input generation is, however, most often independent of the property to be checked, and is instead based on random or user-defined data generation.In this paper, we present property-driven unit testing of functions with numerical inputs and outputs. Alike property-based testing, it allows users to define the properties to be tested for. Contrary to property-based testing, it also uses the property for a targeted generation of test inputs. Our approach is a form of learning-based testing where we first of all learn a model of a given black-box function using standard machine learning algorithms, and in a second step use model and property for test input generation. This allows us to test both predefined functions as well as machine learned regression models. Our experimental evaluation shows that our property-driven approach is more effective than standard property-based testing techniques.

Model-driven Continuous Experimentation on Component-based Software Architectures - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Proceedings of the 18th International Conference on Software Architecture Companion)
To build successful software products, developers continuously have to discover what features the users really need. This discovery can be achieved with continuous experimentation, testing different software variants with distinct user groups, and deploying the superior variant for all users. However, existing approaches do not focus on explicit modeling of variants and experiments, which offers advantages such as traceability of decisions and combinability of experiments. Therefore, our vision is the provision of model-driven continuous experimentation, which provides the developer with a framework for structuring the experimentation process. For that, we introduce the overall concept, apply it to the experimentation on component-based software architectures and point out future research questions. In particular, we show the applicability by combining feature models for modeling the software variants, users, and experiments (i.e., model-driven) with MAPE-K for the adaptation (i.e., continuous experimentation) and implementing the concept based on the component-based Angular framework.
Keywords: continuous experimentation; model-driven; component-based software architectures; self-adaptation

„Beim Ausschneiden zeigen die Wörter mir ihre Bestandteile.“ Memoria als Deutungsöffnung bei Herta Müller - Kißling, Magdalena (Der Deutschunterricht (1))

Bildungsverantwortung im Deutschunterricht. Thesen zu einem bildungsgerechten Literaturunterricht - Kißling, Magdalena (IMST-Newsletter (53))

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Symmetrieverständnis von Anfang an - Häsel-Weide, Uta; Wallner, Melina; Hattermann, M. (Anfangsunterricht für alle Kinder - Willkommen in der Schule!)

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Disjoining and repair strategies of structural joints in automotive lightweight structures - Chudalla, Nick; Bartley, Aurélie; Ditter, Jan; Meschut, Gerson; Wibbeke, Tim Michael

A PLACE FOR A DATA SCIENCE PROJECT IN SCHOOL: BETWEEN STATISTICS AND EPISTEMIC PROGRAMMING - PODWORNY, SUSANNE; Hüsing, Sven; SCHULTE, CARSTEN (STATISTICS EDUCATION RESEARCH JOURNAL)
Aspects of data science surround us in many contexts, for example regarding climate change, air pollution, and other environmental issues. To open the “data-science-black-box” for lower secondary school students we developed a data science project focussing on the analysis of self-collected environmental data. We embed this project in computer science education, which enables us to use a new knowledge-based programming approach for the data analysis within Jupyter Notebooks and the programming language Python. In this paper, we evaluate the second cycle of this project which took place in a ninth-grade computer science class. In particular, we present how the students coped with the professional tool of Jupyter Notebooks for doing statistical investigations and which insights they gained.
Keywords: Education; Statistics and Probability

Microinverter testing update using high power modules: Efficiency, yield, and conformity to a new ”estimation formula” for variation of PV panel size - Krauter, Stefan; Bendfeld, Jörg; Möller, Marius Claus (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
The market for microinverters is growing, especially in Europe. Driven by the strongly rising prices for electricity, many small photovoltaic energy systems are being installed. Since monitoring for these plants is often quite costly, their yields are often not logged. Since 2014, microinverters have been studied at the University of Paderborn. The investigations are divided into indoor and outdoor tests. In the indoor area conversion efficiencies as a function of load have been measured with high accuracy and ranked according to Euro- and CEC weightings. In the outdoor laboratory, the behavior in the real world is tested. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules. Here, the investigations were carried out with modules of the power of 215 Wp until the year 2020. Because of the increasing module power nowadays, modules with an output of 360 Wp are now being used. To assess the influence of PV module size, two extremes have been investigated: A rather small module with 215 Wp - as it has been used 10 years ago, and a brand-new module (2021) offering 360 Wp. Both types of modules contain 60 solar cells in series connection. Appling the low-power modules, the challenge for the different micro-inverters has been during weak-light conditions, using the high-power modules, some inverters temporarily reach their power limits and yield is reduced. A method using a reference configuration of inverter & module and a linear equation resulting in the actual yield, any module & inverter configuration can be characterized by just the two coefficients.

Professionalisierung für inklusiven Mathematikunterricht. Interdisziplinäre Seminarkonzeption zur reflexiven Professionalisierung angehender Mathematiklehrkräfte in der Sekundarstufe - Häsel-Weide, Uta; Seitz, S.; Wallner, Melina; Wilke, Y. (Qualifizierung für Inklusion. Sekundarstufe)

Diagnosegeleitete Förderung im inklusiven Mathematikunterricht der Grundschule – Professionalisierung durch reflektierte Handlungspraxis in der Lehrer*innenbildung. - Hähn, K.; Häsel-Weide, Uta; Scherer, P. (QfI - Qualifizierung für Inklusion)

Model of a Self-Sufficient PV Home using a Hybrid Storage System based on Li-Ion Batteries and Hydrogen Storage with Waste Heat Utilization - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 49th IEEE Photovoltaic Specialists Conference)
This paper provides a hybrid energy system model created in Matlab/Simulink which is based on photovoltaics as its main energy source. The model includes a hybrid energy storage which consists of a short-term lithium-ion battery and hydrogen as long-term storage to ensure autonomy even during periods of low PV production (e.g., in winter). The sectors heat and electricity are coupled by using the waste-heat generated by production and reconversion of hydrogen through an electrolyser respectively a fuel cell. A heat pump has been considered to cover the residual heat demand (for well insulated homes). Within this paper a model of the space heating system as well as the hot water heating system is presented. The model is designed for the simulation and analysis of a whole year energy flow by using a time series of loads, weather and heat profiles as input. Moreover, results of the energy balance within the energy system by simulation of a complete year by varying the orientation (elevation and azimuth) of the PV system and the component sizing, such as the lithium-ion battery capacity, are presented. It turned out that a high amount of heating energy can be saved by using the waste heat generated by the electrolyser and the fuel cell. The model is well suited for the analysis of the effects of different component dimensionings in a hydrogen-based energy system via the overall energy balance within the residential sector.

Hybrid Energy System Model in Matlab/Simulink based on Solar Energy, Lithium-Ion Battery and Hydrogen - Möller, Marius Claus; Krauter, Stefan (Energies / Special Issue "Sustainable Energy Concepts for Energy Transition")
In this paper, a model of a hybrid, hydrogen-based energy system for a household which includes the heating sector is presended. With such an energy system it's possible to enable energy autarky over a whole year based on solar energy. The scope of this study was to present a verified hybrid energy system model created in Simulink which can be used to prospectively size future similar energy systems where hydrogen in combination with a li-ion battery shall be used as energy storage type.

Increased Cognitive Demands Affect Agility Performance in Female Athletes - Implications for Testing and Training of Agility in Team Ball Sports - Büchel, Daniel; Gokeler, Alli; Heuvelmans, Pieter; Baumeister, Jochen (Perceptual and Motor Skills)
Agility, a key component of team ball sports, describes an athlete´s ability to move fast in response to changing environments. While agility requires basic cognitive functions like processing speed, it also requires more complex cognitive processes like working memory and inhibition. Yet, most agility tests restrict an assessment of cognitive processes to simple reactive times that lack ecological validity. Our aim in this study was to assess agility performance by means of total time on two agility tests with matched motor demands but with both low and high cognitive demands. We tested 22 female team athletes on SpeedCourt, using a simple agility test (SAT) that measured only processing speed and a complex agility test (CAT) that required working memory and inhibition. We found excellent to good reliability for both our SAT (ICC = .79) and CAT (ICC =.70). Lower agility performance on the CAT was associated with increased agility total time and split times ( p < .05). These results demonstrated that agility performance depends on the complexity of cognitive demands. There may be interference-effects between motor and cognitive performances, reducing speed when environmental information becomes more complex. Future studies should consider agility training models that implement complex cognitive stimuli to challenge athletes according to competitive demands. This will also allow scientists and practitioners to tailor tests to talent identification, performance development and injury rehabilitation.
Keywords: Sensory Systems; Experimental and Cognitive Psychology

Smart Service für die prädiktive Instandhaltung zentraler Komponenten des Mittelspannungs-Netzes - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Forum Dienstleistungsmanagement)

Method development for increasing the prediction quality of mechanical joining process simulations by friction modeling based on local joining process parameters - Rossel, Moritz Sebastian; Meschut, Gerson (Proceedings of the 6th Conference on Steels in Cars and Trucks)

Koopman analysis of quantum systems - Klus, Stefan; Nüske, Feliks; Peitz, Sebastian (Journal of Physics A: Mathematical and Theoretical)
Koopman operator theory has been successfully applied to problems from various research areas such as fluid dynamics, molecular dynamics, climate science, engineering, and biology. Applications include detecting metastable or coherent sets, coarse-graining, system identification, and control. There is an intricate connection between dynamical systems driven by stochastic differential equations and quantum mechanics. In this paper, we compare the ground-state transformation and Nelson's stochastic mechanics and demonstrate how data-driven methods developed for the approximation of the Koopman operator can be used to analyze quantum physics problems. Moreover, we exploit the relationship between Schrödinger operators and stochastic control problems to show that modern data-driven methods for stochastic control can be used to solve the stationary or imaginary-time Schrödinger equation. Our findings open up a new avenue towards solving Schrödinger's equation using recently developed tools from data science.

CamBench -- Cryptographic API Misuse Detection Tool Benchmark Suite - Schlichtig, Michael; Wickert, Anna-Katharina; Krüger, Stefan; Bodden, Eric; Mezini, Mira
Context: Cryptographic APIs are often misused in real-world applications. Therefore, many cryptographic API misuse detection tools have been introduced. However, there exists no established reference benchmark for a fair and comprehensive comparison and evaluation of these tools. While there are benchmarks, they often only address a subset of the domain or were only used to evaluate a subset of existing misuse detection tools. Objective: To fairly compare cryptographic API misuse detection tools and to drive future development in this domain, we will devise such a benchmark. Openness and transparency in the generation process are key factors to fairly generate and establish the needed benchmark. Method: We propose an approach where we derive the benchmark generation methodology from the literature which consists of general best practices in benchmarking and domain-specific benchmark generation. A part of this methodology is transparency and openness of the generation process, which is achieved by pre-registering this work. Based on our methodology we design CamBench, a fair "Cryptographic API Misuse Detection Tool Benchmark Suite". We will implement the first version of CamBench limiting the domain to Java, the JCA, and static analyses. Finally, we will use CamBench to compare current misuse detection tools and compare CamBench to related benchmarks of its domain.
Keywords: cryptography; benchmark; API misuse; static analysis

Chancen für einen rassismussensiblen Literaturunterricht - didaktische Perspektiven für das Lesen von Menschenzoogeschichten in der Grundschule am Beispiel von Rainer Maria Rilkes Gedicht "Die Aschanti. Jardin d´acclimatation" (1902) - Tönsing, Johanna (Rassismussensibler Literaturunterricht. Neue Perspektiven einer kulturwissenschaftlichen Literaturdidaktik)

(K)eine kinderleichte Gattung: Konsequenzen einer kulturwissenschaftlich informierten Märchendidaktik - Tönsing, Johanna (Interpretationsverfahruen der germanistischen Literaturdidaktik und didaktische Referenzkonzepte)

Bringing Massive Parallelism and Hardware Acceleration to Linear Scaling Density Functional Theory Through Targeted Approximations - Lass, Michael

Über „Gleis 11“ [Dokumentarfilm von 2021] - Tönsing, Johanna (Sammelband über den deutsch-türkischen Film)

Weiblichkeitsdiskurse in der Gegenwartsliteratur und deren Thematisierung im genderorientierten Unterricht - Tönsing, Johanna (Neue Perspektiven einer kulturwissenschaftlichen Literaturdidaktik)

A Large-Scale Study of Usability Criteria Addressed by Static Analysis Tools - Nachtigall, Marcus; Schlichtig, Michael; Bodden, Eric (Proceedings of the 31st ACM SIGSOFT International Symposium on Software Testing and Analysis)
Static analysis tools support developers in detecting potential coding issues, such as bugs or vulnerabilities. Research on static analysis emphasizes its technical challenges but also mentions severe usability shortcomings. These shortcomings hinder the adoption of static analysis tools, and in some cases, user dissatisfaction even leads to tool abandonment. To comprehensively assess the current state of the art, this paper presents the first systematic usability evaluation in a wide range of static analysis tools. We derived a set of 36 relevant criteria from the scientific literature and gathered a collection of 46 static analysis tools complying with our inclusion and exclusion criteria - a representative set of mainly non-proprietary tools. Then, we evaluated how well these tools fulfill the aforementioned criteria. The evaluation shows that more than half of the considered tools offer poor warning messages, while about three-quarters of the tools provide hardly any fix support. Furthermore, the integration of user knowledge is strongly neglected, which could be used for improved handling of false positives and tuning the results for the corresponding developer. Finally, issues regarding workflow integration and specialized user interfaces are proved further. These findings should prove useful in guiding and focusing further research and development in the area of user experience for static code analyses.
Keywords: Automated static analysis; Software usability

FUM - A Framework for API Usage constraint and Misuse Classification - Schlichtig, Michael; Sassalla, Steffen; Narasimhan, Krishna; Bodden, Eric (2022 IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))
Application Programming Interfaces (APIs) are the primary mechanism that developers use to obtain access to third-party algorithms and services. Unfortunately, APIs can be misused, which can have catastrophic consequences, especially if the APIs provide security-critical functionalities like cryptography. Understanding what API misuses are, and for what reasons they are caused, is important to prevent them, e.g., with API misuse detectors. However, definitions and nominations for API misuses and related terms in literature vary and are diverse. This paper addresses the problem of scattered knowledge and definitions of API misuses by presenting a systematic literature review on the subject and introducing FUM, a novel Framework for API Usage constraint and Misuse classification. The literature review revealed that API misuses are violations of API usage constraints. To capture this, we provide unified definitions and use them to derive FUM. To assess the extent to which FUM aids in determining and guiding the improvement of an API misuses detectors' capabilities, we performed a case study on CogniCrypt, a state-of-the-art misuse detector for cryptographic APIs. The study showed that FUM can be used to properly assess CogniCrypt's capabilities, identify weaknesses and assist in deriving mitigations and improvements. And it appears that also more generally FUM can aid the development and improvement of misuse detection tools.
Keywords: API misuses; API usage constraints; classification framework; API misuse detection; static analysis